The Contribution of Philosophical Schools of Thought to the Development of the Islamic Education Curriculum - Supriyanto, Supriyanto; Fuadi, Moh. Ashif (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
Each era experiences significant changes in the field of Islamic education, necessitating the development of a well-structured curriculum grounded in strong philosophical foundations to ensure clear direction and purpose. Therefore, appropriate principles are required to develop the Islamic education curriculum. This study explains the contributions of several educational philosophical schools of thought and their implementation as a foundation for constructing an Islamic education curriculum. The study focuses on three educational philosophies: progressivism, constructivism, and humanism. The method employed is library research using a descriptive analytical approach, presented systematically and objectively. This study finds that integrating progressivism, constructivism, and humanism philosophies in developing Islamic education curricula can enrich pedagogical strategies while preserving core Islamic values. The progressivist approach promotes experiential learning and problem-solving, constructivism emphasizes knowledge construction through reflection and collaboration, while humanism nurtures learners' emotional, moral, and spiritual aspects. These philosophies create a dynamic, interactive, student-centered curriculum relevant to 21st-century needs.